Teasing apart the unique contributions of cognitive and affective predictors of math performance. Issue 1 (28th January 2022) - Silver, Alex M.; Elliott, Leanne; Reynvoet, Bert; Sasanguie, Delphine; Libertus, Melissa E.
Abstract: Math permeates everyday life, and math skills are linked to general educational attainment, income, career choice, likelihood of full‐time employment, and health and financial decision making. Thus, researchers have attempted to understand factors predicting math performance in order to identify ways of supporting math development. Work examining individual differences in math performance typically focuses on either cognitive predictors, including inhibitory control and the approximate number system (ANS; a nonsymbolic numerical comparison system), or affective predictors, like math anxiety. Studies with children suggest that these factors are interrelated, warranting examination of whether and how each uniquely and independently contributes to math performance in adulthood. Here, we examined how inhibitory control, the ANS, and math anxiety predicted college students' math performance ( n  = 122, mean age = 19.70 years). Using structural equation modeling, we find that although inhibitory control and the ANS were closely related to each other, they did not predict math performance above and beyond the effects of the other while also controlling for math anxiety. Instead, math anxiety was the only unique predictor of math performance. These findings contradict previous results in children and reinforce the need to consider affective factors in our discussions and interventions for supporting math performance in college students. Abstract : Work examining individual differences in math performance typically focuses on either cognitive predictors, including inhibitory control and the approximate number system, or affective predictors, like math anxiety. Studies with children suggest these factors are interrelated, warranting examination of whether and how each contributes to math performance in adulthood. Here, we examined how inhibitory control, the ANS, and math anxiety predicted college students' math performance.